A COMPARATIVE STUDY ON ANGLO AND NON-ANGLO ACADEMIC DISCOURSE - Imam Munandar (Asosiasi Dosen Perguruan Tinggi Islam, 2017)
This article showed that Anglo dialogic academic discourse cannot be separated from several aspects such as linear, more personal, writer responsible and focus on form. This writing convention isunderpinned by cultural tradition. Anglo community is influenced by democratic thought pattern belong to Socrates, who stressed the writing as a medium of negotiating meaning and creating knowledge and truth.. Meanwhile, the monologic discourse is found to be produced in non-Anglo communities which have no long democracy tradition. This academic discourse is characterized by impersonal tone, digressiveness, reader responsible and focus on content.. It encourages writer to use writing as a medium of showing knowledge, in which reader do not necessarily need to be guided in explicit and direct way, and assuming that they are intelligent human whom there is nothing much to be directed, guided and explained.